Pelatihan Pembuatan Salad Buah Ibu Pkk Kecamatan Wonotirto, Kabupaten Blitar - Afiyanto, Hendra; Risa Winanti (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2023)
“Everthing has potension”. This sentence according to describe many potencial asset Gununggede village, Blitar district to make community development. The main capital of the development community is changing the people paradigm. This paradigm about how peoples look at the village from advantages and disadvantages. People can see what the big capital in the Gununggede village. From Appresciative Inquiry method which begin from discovery till destiny we have two big potencial Gununggede people. First, fruit in the yard is abundant natural produce and still as a daily consumption. Second, member of PKK has a big potencial, but they activity still not focus at development community with creative economy. From there this event is make a creative economy with make a fruit salad. The benefit of this event is fruit not just consumption but also increase income, make a busy woman to have any activity beside domestic activity.